Frequency of benign tumors after partial nephrectomy and the association between malignant tumor findings and preoperative clinical parameters - Lounová, Veronika; Študent, Vladimír; Purová, Dana; Hartmann, Igor; Vidlář, Aleš; Študent, Vladimír (BMC urology, 2024)
BACKGROUND: Partial nephrectomy (PN) has become the dominant treatment modality for cT1 renal tumor lesions. Tumors suspected of malignant potential are indicated for surgery, but some are histologically classified as benign lesions after surgery. This study aims to analyze the number of benign findings after PN according to definitive histology and to evaluate whether there is an association between malignant tumor findings and individual factors. METHODS: The retrospective study included 555 patients who underwent open or robotic-assisted PN for a tumor in our clinic from January 2013 to December 2020. The cohort was divided into groups according to definitive tumor histology (malignant tumors vs. benign lesions). The association of factors (age, sex, tumor size, R.E.N.A.L.) with the malignant potential of the tumor was further evaluated. RESULTS: In total, 462 tumors were malignant (83%) and 93 benign (17%). Of the malignant tumors, 66% were clear-cell RCC (renal cell carcinoma), 12% papillary RCC, and 6% chromophobe RCC. The most common benign tumor was oncocytoma in 10% of patients, angiomyolipoma in 2%, and papillary adenoma in 1%. In univariate analysis, there was a higher risk of malignant tumor in males (OR 2.13, 95% CI 1.36-3.36, p = 0.001), a higher risk of malignancy in tumors larger than 20 mm (OR 2.32, 95% CI 1.43-3.74, p < 0.001), and a higher risk of malignancy in tumors evaluated by R.E.N.A.L. as tumors of intermediate or high complexity (OR 2.8, 95% CI 1.76-4.47, p < 0.001). In contrast, there was no association between older age and the risk of malignant renal tumor (p = 0.878). CONCLUSIONS: In this group, 17% of tumors had benign histology. Male sex, tumor size greater than 20 mm, and intermediate or high R.E.N.A.L. complexity were statistically significant predictors of malignant tumor findings.
Keywords: dospělí; nádory ledvin; oxyfilní adenom; retrospektivní studie; Humans; Carcinoma, Renal Cell; lidé středního věku; Kidney Neoplasms; Middle Aged; Nephrectomy; karcinom z renálních buněk; Adenoma, Oxyphilic; nefrektomie; angiomyolipom; mužské pohlaví; Kidney tumors; Adult; Angiomyolipoma; ženské pohlaví; Preoperative Period; lidé; Carcinoma, renal cell; Incidence; předoperační období; Aged; senioři; Male; Retrospective Studies; Benign; Pathology; Female